2005
DOI: 10.1159/000083572
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Conservative Voice Treatment in Male-to-Female Transsexuals

Abstract: A voice assessment was performed before and after conservative voice treatment in 3 male-to-female transsexuals and in 2 nontreated transsexuals serving as control persons. The characteristics studied were voice quality, habitual speaking pitch, vocal pitch range, vocal intensity range, maximum phonation time and ‘communicative impairment’, a subjective self-estimation by the patient. Based on these parameters the Friedrich dysphonia index (DI) was calculated. The habitual speaking pitch of the 3 transsexuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 50 publications
1
25
0
2
Order By: Relevance
“…LA's gains were achieved in 15 sessions over 7 months: less time than the 63-year-old who required 88 sessions over 11 months (Mount & Salmon, 1988), but near the range of 8-19 months reported for the 3 participants in their 20 s who underwent similar comprehensive treatment (Mé szá ros et al, 2005). Relatively stable maintenance two-months post therapy is very good compared to the data in Dacakis (2000), which indicated only two of ten participants maintained F0 levels within 3 Hz of discharge levels.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…LA's gains were achieved in 15 sessions over 7 months: less time than the 63-year-old who required 88 sessions over 11 months (Mount & Salmon, 1988), but near the range of 8-19 months reported for the 3 participants in their 20 s who underwent similar comprehensive treatment (Mé szá ros et al, 2005). Relatively stable maintenance two-months post therapy is very good compared to the data in Dacakis (2000), which indicated only two of ten participants maintained F0 levels within 3 Hz of discharge levels.…”
Section: Discussionmentioning
confidence: 75%
“…The anchor words were not defined for the listener so that the variability in how a person might perceive these qualities was not biased by the authors. These terms are subjective but were chosen intentionally for the non-SLP listeners as terms that would not be limited to professional jargon; the terms are occasionally used in other TG voice literature (e.g., Mé szá ros et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus of the pitch boundary between female voices and male voices. Meszaros et al (2005) indicated that the pitch cutoff point between female voices and male voices is around 140-170 Hz. A voice with a pitch median below 140 Hz is usually perceived as a male voice.…”
Section: Pitch-formant Modificationmentioning
confidence: 99%
“…5 However, because hormone treatment for MTF persons does not affect vocal pitch, voice therapy is often sought to develop a more socially acceptable ''feminine'' voice. 6 Research on voice therapy outcomes for MTF TG individuals has shown varying degrees of success in voice feminization. A growing number of studies have examined the acoustic outcomes of voice therapy for MTF TG individuals; but these investigations have typically focused more on outcomes and less on the effects of a specific therapy type.…”
Section: Introductionmentioning
confidence: 99%